2001
DOI: 10.1002/app.1782
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of high‐performance and good water‐soluble melamine–formaldehyde resin

Abstract: ABSTRACT:In this article, high-sulfonated melamine-formaldehyde (HSMF) resins were prepared with a sulfite/melamine (S/M1.5) molar ratio. During the sulfonation process, the reaction temperature and the added velocity of sodium bisulfite affecting the properties of the resin were studied. In the condensation stage, where the pH range is 6.0 and the temperature is about 25°C, the condensation time was prolonged above 24 h. The stability and water solubility of the resin was improved greatly. It is an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Su et al studied which factors affect sulfonation and condensation of highly-sulfonated melamineformaldehyde (sodium metabisulphite/melamine, MTBS/M, molar ratio = 1.5) production and concluded that to achieve resins with good water solubility it was necessary to extend the condensation reaction for 24 hours [11]. Gourdarzian and Rabiee used paraformaldehyde for the preparation of sulfonated melamine-formaldehyde and studied the effect of different degrees of sulfonation with several ratios of MTBS/M (0.6-1.2) [12].…”
Section: Fig 1 the Reactions Between Melamine And Formaldehyde Givimentioning
confidence: 99%
“…Su et al studied which factors affect sulfonation and condensation of highly-sulfonated melamineformaldehyde (sodium metabisulphite/melamine, MTBS/M, molar ratio = 1.5) production and concluded that to achieve resins with good water solubility it was necessary to extend the condensation reaction for 24 hours [11]. Gourdarzian and Rabiee used paraformaldehyde for the preparation of sulfonated melamine-formaldehyde and studied the effect of different degrees of sulfonation with several ratios of MTBS/M (0.6-1.2) [12].…”
Section: Fig 1 the Reactions Between Melamine And Formaldehyde Givimentioning
confidence: 99%
“…33 Additionally, the cross-linking reaction is also easy to be taken place at high temperature, losing the water solubility of hydroxylated melamine. To improve the storage stability of hydroxylated melamine, benzoguanamine 30 and sodium bisulfite 34 were used to modify it to prevent the condensation, but the storage time was still unsatisfactory (4 days or little more). Using methanol to react with hexamethylolmelamine in the presence of acid catalyst can form hexamethoxymethylmelamine (HMMM) and successfully avoid forming insoluble resins.…”
Section: Introductionmentioning
confidence: 99%
“…These admixtures exhibit very good dispersing effects on concrete and can reduce water demand of concrete by up to 25% while maintaining the flow characteristics of concrete. [2][3][4][5][6] Therefore, as superplasticizers, they offer considerable advantages in producing concrete with high workability at much lower water/cement ratio and exhibiting much higher strength.…”
Section: Introductionmentioning
confidence: 99%
“…One key for successful preparation of HPC is the addition of the proper superplasticizer, such as polycarboxylic acid (PC) and water‐soluble sulfonated resins, including sulfonated melamine formaldehyde (SMF) condensate and sulfonated naphthalene formaldehyde (SNF) condensate. These admixtures exhibit very good dispersing effects on concrete and can reduce water demand of concrete by up to 25% while maintaining the flow characteristics of concrete 2–6. Therefore, as superplasticizers, they offer considerable advantages in producing concrete with high workability at much lower water/cement ratio and exhibiting much higher strength.…”
Section: Introductionmentioning
confidence: 99%